2011
DOI: 10.1017/s0007114510004368
|View full text |Cite
|
Sign up to set email alerts
|

Grape juice concentrate prevents oxidative DNA damage in peripheral blood cells of rats subjected to a high-cholesterol diet

Abstract: The goal of the present study was to investigate whether subchronic treatment with grape juice concentrate is able to protect liver and peripheral blood cells against cholesterol-induced injury in rats. The effects of the grape juice concentrate treatment on histopathological changes, immunohistochemistry for cyclo-oxygenase-2 (COX-2), and basal and oxidative DNA damage induced by H 2 O 2 using a single-cell gel (comet) assay were evaluated. Male Wistar rats (n 18) were divided into three groups: group 1 -nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…It is well known that micronucleus formation is linked to increased production of ROS, inhibition of DNA repair, as well as DNA breakage (Hengstler et al 2003;Degrandi et al 2010;Hartwig 2010;Bernhoft 2013). According to Aguiar et al (2011), grape juice polyphenolic compounds were able to limit oxidative DNA damage promoted by free radicals. Our results also demonstrated that grape juice concentrate G8000™ was able to prevent oxidative DNA damage in liver cells induced by hydrogen peroxide in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that micronucleus formation is linked to increased production of ROS, inhibition of DNA repair, as well as DNA breakage (Hengstler et al 2003;Degrandi et al 2010;Hartwig 2010;Bernhoft 2013). According to Aguiar et al (2011), grape juice polyphenolic compounds were able to limit oxidative DNA damage promoted by free radicals. Our results also demonstrated that grape juice concentrate G8000™ was able to prevent oxidative DNA damage in liver cells induced by hydrogen peroxide in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical characterization of grape juice concentrate was performed in a previous study conducted by our research group (Aguiar et al 2011). The following compounds were identified: dimethoxyflavylium, disaccharide, fatty acids (palmitic and linoleic acids), and flavonoids (kaempferol-galactoside, peonidinglucoside, malvidin-glucoside, petunidin 3-O-acetylglucoside, peonidin 3-p-coumaroylglucoside, and malvidin 3-O-p-coumaroylglucoside).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…[130], citrus peel [131], Lycium ruthenicum anthocyanins [132], arti choke leaf extract [133], Ficus microcarpa (L.) [134], grape juice [135], Ficus racemosa [136], and Hibiscus sabadariffa extract [137].…”
Section: Miscellaneous Medicinal Plantsmentioning
confidence: 99%
“…in rat colon after Azoxymethane (AOM). Histopathologic alterations in rat colon of groups submitted to grape juice intake; C: before and after AOM, 1% grape juice intake before and after AOM; D: 1% grape juice intake after AOM, E: 2% grape juice intake before and after AOM; F: 2% grape juice intake after AOM vegetable compounds and their molecular mechanisms of action in order to elucidate the mechanisms underlying the suppression of colorectal carcinogenesis (Aguiar et al, 2011). Resveratrol is a component found in the concentrated grape juice used in the present study and this compound has been shown to inhibit the three stages of carcinogenesis (Aggarwal et al, 2004).…”
Section: Number Of Aberrant Crypt Focimentioning
confidence: 99%